Two Myths and Two Cultural Formations (in Comparison) - Wiśniewska, Lidia (Porównania, 2016)
The article Two Myths and Two Cultural Formations (in comparison) that recalls Jauss’s, Vattimo’s, Lash’s and Steiner’s concepts and indicates too a trans-discipline nature of observation is in the first place focused on the unity between the two myths (God’s and Nature’s ones, also named as modern and archaic myths, and the related paradigms: linear and circular) and the description of the two formations/epochs, that is modernism and postmodernism. This entails a possible reconstruction of two lines to unite the (early) myths and (contemporary) epochs or the reconstruction of the “formation sequences”(dashed and interwoven) determined by the defined methods of how the time and space categories are treated in the described myth and paradigm cognitive patterns.